Review of solar thermal storage techniques - Hayder, Ali Mohammed; Sapit, Azwan; Abed, Qahtan Adnan (Asian Research Publishing Network (ARPN), 2017)
For some time, solar energy has occupied ranked prime position in the renewable energy research field, due to the fact that it is an inexhaustible energy source. However, the main problem of solar energy is that it is an intermittent source, due to it dependence on the period of solar radiation. Consequently, thermal energy storage is considered a perfect option to solve this problem. A thermal energy storage unit works to enhance the conservation of energy and hence, improve the performance of the solar heating system. This paper reviews the literature concerning the usefulness of using the most important two core components in solar heat applications: thermal solar collectors and thermal energy storage systems. It includes a review and discussion of the different kinds of thermal solar collectors and thermal energy storage systems, including a latent heat storage system, a sensible heat storage system, and a hybrid heat storage system. The thermal energy storage systems are studied in terms of efficiency, thermal losses, the thermal conductivity of the material used for storage, and output temperature. The conclusions in this work suggest that latent heat storage through phase change material (PCMs) is better than sensible heat storage, due to the higher thermal energy storage density of PCMs. The conclusions also indicate that the use of paraffin wax as a PCM gives ‎a better performance compared to other phase change materials. In addition, the thermal performance of the solar heating system can also be enhanced by increasing the thermal conductivity of paraffin wax by adding other materials.